A Review on Big Data: Security Challenges - A Sangeerani Devi, (AG Volumes, 2022)
Big data's widespread use has led to rapid growth of data resources, and new data analysis methods like conventional data mining and statistical analysis are helping to fuel this growth. In the world of big data, data from a variety of sources may be analysed, combined, and used in a variety of ways, resulting in new insights. Although each step of the life cycle offers data security and dependability concerns, the protection of personally identifiable information is a vital goal. Big data analytics, in particular, may be used to analyse user preferences, and this information can lead to the violation of personal privacy. The scope of big data is examined, as is the state of the art in big data security research. The concerns and causes influencing security are laid forth. The authors also touch on and expound on methods that protect individual privacy.